2022
DOI: 10.1155/2022/3305773
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Duhuo Jisheng Decoction in Treating Ankylosing Spondylitis: Clinical Evidence and Potential Mechanisms

Abstract: Background. Duhuo Jisheng Decoction (DHJSD) is an ancient compound widely used in the treatment of ankylosing spondylitis (AS). However, its efficacy is controversial, and its mechanism of action is not clear enough. Using meta-analysis and network pharmacology, our study evaluated the clinical efficacy of DHJSD in the treatment of AS and explored its mechanisms of action. Methods. We searched medical databases, including Embase, PubMed, the China National Knowledge Infrastructure databases, Wanfang, and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…It is pungent in smell and bitter in taste, mild in nature, and medicinal in root. AP is one of the TCMs commonly used to treat ankylosing spondylitis, 6 knee osteoarthritis, 7 lumbar disc protrusion, 8 rheumatoid arthritis, 9 and other diseases, with significant clinical effects. At present, the 1 Tibet University Medical College, Lhasa, China 2 studies on AP are limited to the application of prescriptions such as Du Huo Jisheng Decotion, and there is no specific single drug report, and its pharmacological mechanism needs further excavation and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is pungent in smell and bitter in taste, mild in nature, and medicinal in root. AP is one of the TCMs commonly used to treat ankylosing spondylitis, 6 knee osteoarthritis, 7 lumbar disc protrusion, 8 rheumatoid arthritis, 9 and other diseases, with significant clinical effects. At present, the 1 Tibet University Medical College, Lhasa, China 2 studies on AP are limited to the application of prescriptions such as Du Huo Jisheng Decotion, and there is no specific single drug report, and its pharmacological mechanism needs further excavation and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%